Ionic‐electronic dual‐conductor interface engineering and architecture design in layered lithium‐rich manganese‐based oxides - Youyou Fang; Yuefeng Su; Jinyang Dong; Jiayu Zhao; Haoyu Wang; Ning Li; Yun Lu; Yujia Wu; Wenbo Li; Ni Yang; Xiaojuan Wu; Feng Wu; et al. (Carbon Energy)
Abstract The burgeoning growth in electric vehicles and portable energy storage systems necessitates advances in the energy density and cost‐effectiveness of lithium‐ion batteries (LIBs), areas where lithium‐rich manganese‐based oxide (LLO) materials naturally stand out. Despite their inherent advantages, these materials encounter significant practical hurdles, including low initial Coulombic efficiency (ICE), diminished cycle/rate performance, and voltage fading during cycling, hindering their widespread adoption. In response, we introduce an ionic‐electronic dual‐conductive (IEDC) surface control strategy that integrates an electronically conductive graphene framework with an ionically conductive heteroepitaxial spinel Li4Mn5O12 layer. Prolonged electrochemical and structural analyses demonstrate that this IEDC heterostructure effectively minimizes polarization, mitigates structural distortion, and enhances electronic/ionic diffusion. Density functional theory calculations highlight an extensive Li+ percolation network and lower Li+ migration energies at the layered‐spinel interface. The designed LLO cathode with IEDC interface engineering (LMOSG) exhibits improved ICE (82.9% at 0.1 C), elevated initial discharge capacity (296.7 mAh g−1 at 0.1 C), exceptional rate capability (176.5 mAh g−1 at 5 C), and outstanding cycle stability (73.7% retention at 5 C after 500 cycles). These findings and the novel dual‐conductive surface architecture design offer promising directions for advancing high‐performance electrode materials.